CHAOS SCIENCE & THE PARADOX IN ELECTRO CARDIOGRAPHIC INTERPRETATIONS - Kumar, Arunachalam (Journal of Health and Allied Sciences NU, 2011)
The application of the radically and new non-linear science of 'chaos' has been slow in acceptance in the medical field; each and every diagnostic, investigative and pharmaco-therapeutic process involved in health science is dictated by direct Newtonian tenets of causeeffect and linear mathematical derivations. Exclusive and total dependence on scalar models have compartmentalized patient profiles into rigid cocoons such as age, sex, weight, height, physiological and biochemical evaluations making interventional therapeutic regimens solely dictated by our over-riding choice to use scales of convenience for every single one of our evaluation, assessment and treatment criteria.The paradoxical and skewed results in seemingly normal processes, when viewed through 'chaos' systems, show how wrong our total reliance on scale and linear applications are! As an example of how terribly paradoxical inferences can be, I have electrocardiography, a common and widely used diagnostic process